PENGARUH RETURN ON ASSET (ROA) DAN NET PROFIT MARGIN (NPM) TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Juwita, Rukmi; Novita Pardosi, Mawar (LAND JOURNAL, 2024)
Return on Assets is a ratio that takes into account the amount of net profit after tax from the total assets. Net Profit Margin is a ratio that takes into account the amount of net profit after tax from sales. Researchers have a goal to examine the state of Return on Assets and Net Profit Margin in the Automotive and Component Sub-Sector companies and also examine whether or not there is an influence on Return on Assets and Net Profit Margin partially or simultaneously on profit growth in the Automotive and Sub-Sector companies. Components listed on the Indonesia Stock Exchange. This study uses a quantitative method in the form of an associative problem formulation with a causal relationship, and by using secondary data sources. Researchers took 33 samples in the form of annual financial reports or annual reports of companies in the Automotive and Components Sub-Sector listed on the Indonesia Stock Exchange. Data analysis techniques used by researchers are; descriptive statistical analysis, product moment correlation, multiple correlation, multiple linear regression, coefficient of determination, partial test, simultaneous test. The results of partial hypothesis testing between Return on Assets and Net Profit Margin have no effect on profit growth. And simultaneously there is no significant effect between Return on Assets and Net Profit Margin on profit growth. The results of R Square, where the percentage value of the influence of the independent variable simultaneously on the dependent variable is 11.1% and the rest is 88.9% where the rest is influenced by other variables and factors.